2014
DOI: 10.1186/1471-2296-15-52
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of nursing in Australian general practice: a comparative analysis of workforce surveys ten years on

Abstract: BackgroundNursing in Australian general practice has grown rapidly over the last decade in response to government initiatives to strengthen primary care. There are limited data about how this expansion has impacted on the nursing role, scope of practice and workforce characteristics. This study aimed to describe the current demographic and employment characteristics of Australian nurses working in general practice and explore trends in their role over time.MethodsIn the nascence of the expansion of the role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
99
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(105 citation statements)
references
References 21 publications
2
99
0
3
Order By: Relevance
“…This creates diverse and exciting opportunities for PHCNs to step into a range of roles in men's healthcare services with significant implications (e.g. increased education requirement in health promotion and chronic disease management) in providing clinical care (Halcomb et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This creates diverse and exciting opportunities for PHCNs to step into a range of roles in men's healthcare services with significant implications (e.g. increased education requirement in health promotion and chronic disease management) in providing clinical care (Halcomb et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…) to practice nursing where there has been a significant increase in EN numbers (Halcomb et al. ). However, no study was found which defined the scope of practice for ENs within community health or in the home setting.…”
Section: Discussionmentioning
confidence: 99%
“…Given the nature of general practice as small businesses a more sophisticated sampling strategy was not possible (Halcomb et al . ).…”
Section: The Studymentioning
confidence: 97%
“…This relatively unplanned approach to workforce development has led to several challenges for the nursing profession, in particular relating to: the role of nurses in general practice; the nurses’ scope of practice; and their subsequent opportunities for continuing professional development (Halcomb et al . ).…”
Section: Introductionmentioning
confidence: 97%